The vital role of law in fighting Australia's food waste. (September 2022) - Bird, Susan; Amarakoon, Upamali; Liang, Xiaoyan; Pearson, David
Food waste is a global problem, with significant environmental, social and economic implications. A concerted effort that engages all world governments would be an optimal approach to address food waste. While there has been some international agreement, strategies on how to reduce food waste remain the purview of national, state and local governments. In this article, we explore the Australian government's commitment to fighting food waste, and strategies to realise its vision to halve food waste by 2030. Arguing that voluntary action may not be sufficient to reach this goal, we highlight the role that law can play in fighting food waste.